2020
DOI: 10.1111/1462-2920.15232
|View full text |Cite
|
Sign up to set email alerts
|

Putative degraders of low‐density polyethylene‐derived compounds are ubiquitous members of plastic‐associated bacterial communities in the marine environment

Abstract: Summary It remains unknown whether and to what extent marine prokaryotic communities are capable of degrading plastic in the ocean. To address this knowledge gap, we combined enrichment experiments employing low‐density polyethylene (LDPE) as the sole carbon source with a comparison of bacterial communities on plastic debris in the Pacific, the North Atlantic and the northern Adriatic Sea. A total of 35 operational taxonomic units (OTUs) were enriched in the LDPE‐laboratory incubations after 1 year, of which 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 65 publications
(102 reference statements)
0
10
0
Order By: Relevance
“…So far, most environmental studies did not find conclusive differences between the microbial communities on plastic vs. glass surfaces 12,14,[57][58][59] . On the other hand, studies in enclosed or semi-enclosed systems often showed differential taxonomic representation [15][16][17]60 . These differences between the two types of studies may be due to the milder masking effects of environmental factors under controlled lab conditions.…”
Section: Discussionmentioning
confidence: 99%
“…So far, most environmental studies did not find conclusive differences between the microbial communities on plastic vs. glass surfaces 12,14,[57][58][59] . On the other hand, studies in enclosed or semi-enclosed systems often showed differential taxonomic representation [15][16][17]60 . These differences between the two types of studies may be due to the milder masking effects of environmental factors under controlled lab conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, several researchers have obtained microplastic-associated bacterial community having plastic-degrading potentials in the field investigation. For example, the plastisphere bacterial communities on PET surfaces in the North Sea 33 , bacterial biofilms associated with PE, PP and glass during an in-situ incubation experiment taking place in the northern Adriatic Sea 27 . However, these studies mainly focus on the community structures and dynamics of bacteria on the surfaces of plastics, the metabolic pathways and associated mechanistic processes involved in the biodegradation of plastics are yet to be characterized.…”
Section: Discussionmentioning
confidence: 99%
“…However, as compared to the extensive studies about PET-degrading bacteria and enzymes 14, 18, 19, 2426 , the researches about PE degradation mediated by microorganisms lag well behind and the degradation efficiency using a single strain or enzyme is still too low to meet the industrial applications requirements. Alternatively, using microbial community to degrade PE might be a good choice given their inherent multiple robust function among synergistic effect of different species 27 . Actually, the construction of artificial microbial consortia has opened a new horizon in environment bioremediation in terms of removing hard biodegradable harmful compounds 28 .…”
Section: Introductionmentioning
confidence: 99%
“…These aspects of jellyfish are largely unexplored and should be addressed more intensively in future studies. These types of compounds and pollutants can evoke specific type of metabolic pathways in microbes with important implications for ecosystem functioning (Dombrowski et al 2016; Li et al 2019; Pinto et al 2020). Since jellyfish blooms likely increase in the future in several anthropogenically impacted coastal zones, where also higher concentrations of pollutants can be expected than in open waters, jellyfish might be substantially biomagnifying heavy metals and pollutants (Caurant et al 1999; Sun et al 2017; Macali et al 2018; Iliff et al 2020).…”
Section: Jellyfish As Sink and Source Of Ommentioning
confidence: 99%